2001
DOI: 10.3109/01674820109049973
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of violence investigated in a pregnant population in Sweden

Abstract: All women registered for antenatal care within a Swedish municipality during a 6-month period were assessed regarding acts of violence. The Abuse Assessment Screen was used on two occasions during pregnancy, and once between 4 and 20 weeks after delivery. The efficacy of repeated interviews was investigated, and characteristics of abused and non-abused women were compared. The participation rate was 93% (1038 women). Physical abuse by a close acquaintance or relative during or shortly after pregnancy was repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
32
0
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 21 publications
8
32
0
1
Order By: Relevance
“…These figures are similar to a previous Swedish study conducted in Uppsala where 2.8% (n = 29) admitted physical abuse by a close acquaintance the year before pregnancy, during pregnancy or 20 weeks postpartum [24]. Nevertheless, it is difficult to compare these results due to the use of different methods and definitions and the lack of separation of history of violence before or after pregnancy from violence during pregnancy.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…These figures are similar to a previous Swedish study conducted in Uppsala where 2.8% (n = 29) admitted physical abuse by a close acquaintance the year before pregnancy, during pregnancy or 20 weeks postpartum [24]. Nevertheless, it is difficult to compare these results due to the use of different methods and definitions and the lack of separation of history of violence before or after pregnancy from violence during pregnancy.…”
Section: Discussionsupporting
confidence: 81%
“…Participation recruitment was mostly performed during the first and early second trimesters of pregnancy, and therefore, the results reflect responses to questions about abuse that were posed only once and at this particular time. It has been shown that repeated questioning increases the likelihood of disclosing experiences of physical violence [24,42]. Further, the true prevalence of abuse may be difficult to determine because of fears concerning abuse escalation, if the abuse were to become known by the perpetrator [21].…”
Section: Discussionmentioning
confidence: 99%
“…A prevalence of around 20% [1][2][3] makes childhood sexual abuse (CSA) experiences an important problem in prenatal care, whose frequency is comparable to those of other risk factors for unfavorable pregnancy outcome such as gestational diabetes or hypertensive disorders in pregnancy [4]. Between 74% and 96% of women exposed to CSA present physical and emotional long-term consequences [5].…”
Section: Introductionmentioning
confidence: 99%
“…1 Studies undertaken in Europe have shown a lower prevalence (1.3-5.8 %). [2][3][4][5][6][7] The reproductive years represent a particularly vulnerable period for women regarding susceptibility to potential health hazards, both for her own health (including injuries, unwanted pregnancies, and other sexual and reproductive health problems) and for the development of the foetus.…”
Section: Introductionmentioning
confidence: 99%